Multidrug-resistant tuberculosis/rifampicin-resistant tuberculosis: Principles of management - Rajendra Prasad; Nikhil Gupta; Amitabh Banka (Lung India, 2018)
Multidrug-resistant tuberculosis (MDR-TB)/rifampicin-resistant TB (RR-TB) is human-made problem and emerging due to poor management of TB and is a threat to control of TB. Early suspicion and diagnosis are important. Culture and drug susceptibility testing are gold standards, but newer molecular methods help in rapid diagnosis. Once diagnosed, prompt treatment should be started, preferably under direct observation. Treatment can be standardized or individualized. Conventional regimen takes up to 24 months but recently shorter regimen of up to 12 months was introduced in specific subset of MDR-TB/RR-TB patients. Management of MDR-TB/RR-TB is complicated, costlier, and challenging and is a concern for human health worldwide. It must be emphasized that optimal treatment of MDR-TB/RR-TB alone is not sufficient. Efforts must be made to ensure effective use of first- and second-line anti-TB drugs.